Extension of the Multipole Approach to Random Metamaterials. (25th November 2012) - Chipouline, A.; Sugavanam, S.; Petschulat, J.; Pertsch, T.
Abstract : Influence of the short-range lateral disorder in the meta-atoms positioning on the effective parameters of the metamaterials is investigated theoretically using the multipole approach. Random variation of the near field quasi-static interaction between metaatoms in form of double wires is shown to be the reason for the effective permittivity and permeability changes. The obtained analytical results are compared with the known experimental ones.